Nitrogen-loss and carbon-footprint reduction by plant-rhizosphere exudates - Lu Y.; Kronzucker H.J.; Yu M.; Shabala S.; Shi W.
Low-carbon approaches to agriculture constitute a pivotal measure to address the challenge of global climate change. In agroecosystems, rhizosphere exudates are significantly involved in regulating the nitrogen (N) cycle and facilitating belowground chemical communication between plants and soil microbes to reduce direct and indirect emissions of greenhouse gases (GHGs) and control N runoff from cultivated sites into natural water bodies. Here, we discuss specific rhizosphere exudates from plants and microorganisms and the mechanisms by which they reduce N loss and subsequent N pollution in terrestrial and aquatic environments, including biological nitrification inhibitors (BNIs), biological denitrification inhibitors (BDIs), and biological denitrification promoters (BDPs). We also highlight promising application scenarios and challenges in relation to rhizosphere exudates in terrestrial and aquatic environments. © 2023 Elsevier Ltd
Keywords: AMMONIA VOLATILIZATION; BIOLOGICAL DENITRIFICATION PROMOTERS; BIOLOGICAL NITRIFICATION INHIBITORS; NITROUS OXIDE; ROOT EXUDATES; SUSTAINABLE AGRICULTURE